Alasan Pria Dalam Membeli Sampo Wanita: Studi Keputusan Pembelian - Walangitan, Misael Aldo; Rondonuwu, Bervie Fransel; Pontorondo, Immanuel Christian; Sinaga, Floren Agnesia (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research aimedto determine the reasons behind men's purchasing decisions for women's shampoo products. This research was conducted in the Manado State Polytechnic environment, with a sample consisting of male students of the Manado State Polytechnic. The research method used is qualitative, with a bold interview approach via Google Forms. This research identifies several reasons that influence men's purchasing decisions regarding women's shampoo, which are then determined to be factors that influence purchasing decisions. The factors identified are product quality, smell andsocial influence. These findings provide deeper insight into male consumers' behaviortowards products marketed to women.